Respiratory tract exacerbations revisited: Ventilation, inflammation, perfusion, and structure (VIPS) monitoring to redefine treatment. (3rd September 2015) - Tiddens, Harm A.W.M.; Stick, Stephen M.; Wild, Jim M.; Ciet, Pierluigi; Parker, Geoffrey J.M.; Koch, Armin; Vogel‐Claussen, Jens
Summary: For cystic fibrosis (CF) patients older than 6 years there are convincing data that suggest respiratory tract exacerbations (RTE) play an important role in the progressive loss of functional lung tissue. There is a poor understanding of the pathobiology of RTE and whether specific treatment of RTE reduces lung damage in the long term. In addition, there are limited tools available to measure the various components of CF lung disease and responses to therapy. Therefore, in order to better understand the impact of RTE on CF lung disease we need to develop sensitive measures to characterize RTE and responses to treatment; and improve our understanding of structure‐function changes during treatment of RTE. In this paper we review our current knowledge of the impact of RTE on the progression of lung disease and identify strategies to improve our understanding of the pathobiology of RTE. By improving our knowledge regarding RTE in CF we will be better positioned to develop approaches to treatment that are individualized and that can prevent permanent structural damage. We suggest the development of a ventilation, perfusion, inflammation and structure (VIPS)‐MRI suite that supplies the clinician with data on ventilation, inflammation, perfusion, and structure in one MRI session. VIPS‐MRI could be an important step to better understand the factors that contribute to and limit treatment efficacy of RTE.Pediatr Pulmonol. 2015; 50:S57–S65. © 2015 Wiley Periodicals, Inc.